Assessment of patients’ perception and satisfaction with extemporaneous compounding service in ALERT hospital, Ethiopia - Beyene Hirpina; Muluken Nigatu Selam; Atalay Mulu Fentie; Minychel Wale; Aychew Mekuriaw Tegegne; Samuel Abera (BMC Health Services Research)
Abstract Background Extemporaneous compounding for dermatological use is an important therapeutic alternative for patients whose clinical needs are not met by approved drug products circulated in the market. Evaluating patients’ perceptions and levels of satisfaction towards such services is an important factor for the adherence of patients and maintaining the quality of healthcare services. The current study aimed to assess patients’ perception and level of satisfaction with the compounding service and extemporaneous preparations rendered at ALERT hospital. Methods An institution-based cross-sectional study was conducted among patients receiving compounding pharmacy services at ALERT hospital, Addis Ababa, Ethiopia from 10th April to 10th May 2023. A consecutive sampling technique was used to recruit the study participants. Data were collected using an interviewer-administered structured questionnaire, entered into the EPI info, exported and analyzed using SPSS. Multivariate linear regression analysis was performed to determine possible predictors of patient satisfaction and p-value < 0.05 considered as statistically significant. Results A total of 422 patients recruited and most were predominantly females (64.4%) and aged between 26 and 35 years (38.4%). Nearly 2/3rd had a previous history of compounded medicine use. Majority of the respondents strongly agreed with their satisfaction with price (51.4%), the adequacy of information provided (67.8%), the ease and smoothness of communication with staff (72.0%), and the politeness and supportiveness of staff (73.2%). However, 39.1% of participants disagreed towards the fairness of compounding service waiting time. The overall positive perception and satisfaction level of patients at ALERT hospital receiving the compounding service for their dermatological preparations were 84.41% and 78.57%, respectively. Conclusions The patients’ perception and satisfaction towards the compounding service at ALERT hospital indicated that the dermatological preparations and the services are optimal. Hence, health professionals and the hospital management should take further steps to improve service quality and enhance patient satisfaction.